PENGOLAHAN LIMBAH RUMAH TANGGA MENJADI PUPUK KOMPOS DENGAN SISTEM BIOPORI DI DESA JEMBATAN KEMBAR TIMUR, LOMBOK BARAT - Pratiwi, Dewa Ayu Agung Ratih; Haq, Ayu Kirana; Thoriq, Muhammad; Adi, Ilham Ananda Krista; Azzahra, Sakinah; Tiaskara, Nazrina Dwi; Nurhayati, Nurhayati; At-Thoriq, Muhammad Ari; Diwangkari, Fanashya Diva Radya; Nurfajilah, Nurfajilah; Buhari, Nurliah (Universitas Mataram, 2024)
Kuliah Kerja Nyata (KKN) is one form of implementation of the Tri Dharma of higher education, namely community service. In the KKN activities carried out in Jembatan Kembar Timur Village, Lembar District, the Mataram University KKN student group carried out various activities with the main target of handling problems in the field. In the KKN PMD activities carried out in Jembatan Kembar Timur Village, Lembar District, West Lombok Regency, the KKN PMD Student group of Mataram University carried out various activities with the main target of addressing problems in the context of Green Economy. Jembatan Kembar Timur Village is a village where most of the population earns a living as farmers and breeders. In this village there is one hamlet that is located on a high hill, the hamlet is Tibu Lilin Hamlet which is the only hamlet in Jembatan Kembar Timur Village that is located on a hill. There are still many people who are not aware of the importance of cleanliness and how to manage waste properly. Therefore, the purpose of implementing this KKN PMD activity is to overcome several problems related to the community's difficulty in minimizing household waste, and the community's dependence on the use of chemical fertilizers which can have a negative impact on crop yields and damage the soil, lack of community knowledge about the use of compost. There are several methods carried out, namely surveys and socialization, as well as training in making fertilizer from household waste. Household waste is often a complex problem in various regions, including in Jembatan Kembar Timur Village, West Lombok. One solution to overcome this problem is to process organic waste into compost using a biopore system. This KKN PMD UNRAM activity aims to identify the effectiveness of the biopore system in processing household waste into compost, and analyze its impact on soil quality and the environment in Jembatan Kembar Timur Village. The methods used include making biopore holes, filling in organic waste, and monitoring the decomposition process. The results showed that the biopore system is able to accelerate the decomposition process of organic waste, produce quality compost, and provide significant benefits in improving soil fertility and reducing the volume of waste that must be disposed of. In addition, the implementation of this system at the household level is also proven to increase public awareness of the importance of environmentally friendly waste management. Thus, the biopore system can be a sustainable solution in household waste management in rural areas.